2020
DOI: 10.12659/msm.921700
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamic Neural Activity in the Default Mode Network in Lung Cancer Patients After Chemotherapy

Abstract: Background: Few studies have examined functional brain changes specifically associated with chemotherapy (CTx) in patients with lung cancer. This prospective longitudinal research aimed to explore the change in intrinsic brain activity by investigating patients with lung cancer after CTx. Material/Methods: Sixteen patients and 20 healthy individuals were enrolled in this study. The amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo), dynamic amplitude of low-frequency fluctuation (dALFF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…However, in our study, the region showing significant differences in dynamic VMHC (i.e., OFC) had no overlap with those in static VMHC. This finding is inconsistent with Chen et al ( 2020), but in line with several studies using other static and dynamic metrics (Han et al, 2018;You et al, 2020). We hypothesize that this discrepancy might be associated with the distinct implications between static and dynamic analyses.…”
Section: Discussioncontrasting
confidence: 94%
“…However, in our study, the region showing significant differences in dynamic VMHC (i.e., OFC) had no overlap with those in static VMHC. This finding is inconsistent with Chen et al ( 2020), but in line with several studies using other static and dynamic metrics (Han et al, 2018;You et al, 2020). We hypothesize that this discrepancy might be associated with the distinct implications between static and dynamic analyses.…”
Section: Discussioncontrasting
confidence: 94%
“…Several studies about brain function changes in lung cancer patients have demonstrated the feasibility of fMRI ( 5 , 6 ). You et al reported that the dynamic brain activity of patients with chemotherapy significantly decreased in the default-mode network (DMN) region ( 7 ), and Hu et al found that the dynamic functional connectivity variability in patients with chemotherapy was significantly reduced in several brain regions ( 8 ). Simo et al also reported the DMN functional connectivity decreases in patients with lung cancer ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased fALFF was identified in the left precuneus of breast cancer patients received a chemotherapy regimen of docetaxel and cyclophosphamide ( 26 ). Lung cancer patients before chemotherapy demonstrated decreased ALFF in the right posterior cingulate cortex when compared with patients after chemotherapy including pemetrexed, gemcitabine, cisplatin, nedaplatin, docetaxel and etoposide ( 27 ). Therefore, we speculated that fALFF might be a promising imaging indicator for exploring the central pathological mechanism of cognitive impairment in CRC patients after chemotherapy.…”
Section: Introductionmentioning
confidence: 87%